ANALISIS EMOSI TOKOH LAIL PADA NOVEL HUJAN KARYA TERE LIYE - Sumiharti Sumiharti; Janita Debora Parapat (Universitas Batanghari, 2019)
The purpose of this research is to describe the emotion of Lail character in the novel Hujan by Tere Liye which consists of 7 aspects, they are; the concept of guilt, the concept of hidden guilt, punishing self, feeling of ashamed, sadness, hate, and love. This research is qualitative descripptive by using structural approach. The data of this research is verbal data in the forms of sentences from the whole story or dialog paragraphs which have emotional values on the Lain character in the novel Hujan by Tere Liye. Based on the analysis of the data, it can be found that there are 52 expressions occured from the Lail character. There is 5 expressions which represents the concept of guilt, there is 5 expressions which represents the concept of hidden guilt, 4 expressions which represents punishing self, 9 expressions which represents feeling of ashamed, 12 expressions which represents sadness, 11 expressions which represents hate, and 6 expressions which represents love. So, it can be concluded that those 7 aspects occured in the character of Lail in the novel Hujan by Tere Liye.